WNT1‐inducible‐signaling pathway protein 1 regulates the development of kidney fibrosis through the TGF‐β1 pathway. Issue 11 (7th September 2020) - Wang, Bo; Ding, Xiaoming; Ding, Chenguang; Tesch, Greg; Zheng, Jin; Tian, PuXun; Ricardo, Sharon; Shen, Hsin‐Hui; Xue, Wujun
Abstract: Fibrosis is a pathological feature of chronic kidney disease and its progression correlates with declining renal function. Kidney fibrosis is driven by multiple profibrotic factors. This project examined the regulatory function of WNT1‐inducible‐signaling pathway protein 1 (WISP1) in the development of kidney fibrosis. Induction of WISP1 by transforming growth factor beta 1 (TGF‐β1), and the role of WISP1 in TGF‐β1/Smad signaling and fibrotic responses, was examined in multiple kidney cells. Kidney expression of WISP1 was examined in mouse models of unilateral ureter obstruction (UUO) and streptozotocin‐induced diabetic nephropathy. WISP1 antibody was administered to UUO mice during the induction of kidney injury and the impact on kidney fibrosis was examined. WISP1 expression was upregulated in both mouse models. TGF‐β1‐induced expression of WISP1 and profibrotic genes in cultured kidney cells via TGF‐βR1. Recombinant WISP1‐induced expression of TGF‐βR1 in kidney cells. Suppression of WISP1 by shRNA or neutralizing antibody reduced TGF‐β1‐mediated activation of Smad3, fibrotic gene expression, and fibroblast proliferation. Treatment with WISP1 antibody inhibited the development of kidney fibrosis in UUO mice. WISP1 mediates the profibrotic effects of TGF‐β1 in kidney cells and in kidney disease. Pharmacological blockade of WISP1 exhibits potential as a novel therapy for inhibiting kidney fibrosis.